Revision of the genus Eumorphobotys with descriptions of two new species (Lepidoptera, Crambidae, Pyraustinae) - Chen, Kai; Zhang, Dandan; Stănescu, Mihai (Zootaxa, 2018)
The genus Eumorphobotys Munroe & Mutuura (1969) comprises two species that have been found in southern China. Two new species, E. concavuncus sp. n. and E. horakae sp. n., are described from southwest China. In appearance, this genus also resembles Calamochrous Lederer, 1863, Sclerocona Meyrick, 1890, Prodasycnemis Warren, 1892, and Loxoneptera Hampson, 1896. In order to evaluate the generic placement of the new taxa, the phylogeny of Eumorphobotys species and several species representing the potential related genera based on sequence data of COI, 16S rRNA, EF-1α and 28S rRNA gene regions were reconstructed and the taxonomy of these genera based on morphological characters was re-assessed. The results are as follows: (i) the monophyly of Eumorphobotys is well supported; (ii) Loxoneptera is paraphyletic. Two species of Calamochrous were recovered as terminal lineages within Loxoneptera; (iii) the clade comprising species of Loxoneptera and Calamochrous is in the sister position to Eumorphobotys with a robust support; (iv) species of Loxoneptera and Calamochrous resemble Eumorphobotys in the wing shape and the porrect labial palpus but differ in genitalia structures. The relationships of these genera are discussed; (v) two new species, E. concavuncus sp. n. and E. horakae sp. n., are described, Calamochrous obscuralis (Caradja, 1925) syn. n. is synonymized with E. eumorphalis (Caradja, 1925) based on the male genitalia and the adults and genitalia of all species (except the female of E. horakae sp. n.) are illustrated.